Gonadotropin-releasing hormone analogs: Understanding advantages and limitations - Pratap Kumar; Alok Sharma (Wolters Kluwer Medknow Publications, 2014)
Pituitary stimulation with pulsatile gonadotropin-releasing hormone (GnRH) analogs induces both follicle-stimulating hormone (FSH) and luteinizing hormone (LH). Pituitary gonadotropin secretions are blocked upon desensitization when a continuous GnRH stimulus is provided by means of an agonist or when the pituitary receptors are occupied with a competitive antagonist. GnRH antagonists were not available originally; therefore, prolonged daily injections of agonist with its desensitizing effect were used. Today, single- and multiple-dose injectable antagonists are also available to block the LH surge and thus to cause desensitization. This review provides an overview of the use of GnRH analogs which is potent therapeutic agents that are considerably useful in a variety of clinical indications from the past to the future with some limitations. These indications include management of endometriosis, uterine leiomyomas, hirsutism, dysfunctional uterine bleeding, premenstrual syndrome, assisted reproduction, and some hormone-dependent tumours, other than ovulation induction.